2021
DOI: 10.1038/s41467-021-24428-7
|View full text |Cite
|
Sign up to set email alerts
|

NiFeOx decorated Ge-hematite/perovskite for an efficient water splitting system

Abstract: To boost the photoelectrochemical water oxidation performance of hematite photoanodes, high temperature annealing has been widely applied to enhance crystallinity, to improve the interface between the hematite-substrate interface, and to introduce tin-dopants from the substrate. However, when using additional dopants, the interaction between the unintentional tin and intentional dopant is poorly understood. Here, using germanium, we investigate how tin diffusion affects overall photoelectrochemical performance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 71 publications
9
78
1
Order By: Relevance
“…Photoelectrochemical (PEC) water splitting exploits a promising mechanism that generates clean energy by which water produces hydrogen and oxygen gases with the help of photogenerated electron–hole pairs . Hematite is a promising PEC material due to its abundant quantity, low cost, appropriate band gap, and excellent stability in an aqueous solution. However, the application of hematite has been limited due to its very low solar-to-hydrogen conversion efficiency of 4–5% compared to the theoretical efficiency of 15.5% because of a high recombination rate, low bulk conductivity, low surface reaction kinetics, and sluggish charge transport property. Many methods have been suggested to address these drawbacks, including elemental doping, heterojunction construction, development of nanostructures, and surface passivation. Among them, doping with various heteroatoms such as Ti, Si, Ge, Sn, and other dopants has been widely applied to produce high-efficiency photoelectrodes by resolving the low bulk conductivity issue and sluggish surface reaction kinetics of hematite.…”
Section: Introductionsupporting
confidence: 94%
“…Photoelectrochemical (PEC) water splitting exploits a promising mechanism that generates clean energy by which water produces hydrogen and oxygen gases with the help of photogenerated electron–hole pairs . Hematite is a promising PEC material due to its abundant quantity, low cost, appropriate band gap, and excellent stability in an aqueous solution. However, the application of hematite has been limited due to its very low solar-to-hydrogen conversion efficiency of 4–5% compared to the theoretical efficiency of 15.5% because of a high recombination rate, low bulk conductivity, low surface reaction kinetics, and sluggish charge transport property. Many methods have been suggested to address these drawbacks, including elemental doping, heterojunction construction, development of nanostructures, and surface passivation. Among them, doping with various heteroatoms such as Ti, Si, Ge, Sn, and other dopants has been widely applied to produce high-efficiency photoelectrodes by resolving the low bulk conductivity issue and sluggish surface reaction kinetics of hematite.…”
Section: Introductionsupporting
confidence: 94%
“…Although the loading of the OECs and passivation layer improves the stability of the photoanode, introducing interfacial defects in the process of supporting the OECs often worsens the photoanode stability [89,90]. To address the interfacial defects between the OECs and photoanode interface, researchers usually support the OECs by in situ techniques or by introducing an interfacial layer [91,92].…”
Section: Fe 2 Omentioning
confidence: 99%
“…23,24 Recently, several theoretical and experimental studies have highlighted the beneficial effect of germanium (Ge) as an additive to improve the photocurrent of hematite photoanodes. 25–31 After analyzing the experimental studies, we observed a clear dependence of the photoelectrochemical performance of the hematite photoanodes on the synthesis route used to introduce Ge. 31 This dependence is associated with the low chemical compatibility between α-Fe 2 O 3 and GeO 2 .…”
Section: Introductionmentioning
confidence: 98%